Effects of estrogen on growth plate senescence and epiphyseal fusion - Weise, Martina (The National Academy of Sciences, 2001)
Estrogen is critical for epiphyseal fusion in both young men and women. In this study, we explored the cellular mechanisms by which estrogen causes this phenomenon. Juvenile ovariectomized female rabbits received either 70 μg/kg estradiol cypionate or vehicle i.m. once a week. Growth plates from the proximal tibia, distal tibia, and distal femur were analyzed after 2, 4, 6, or 8 weeks of treatment. In vehicle-treated animals, there was a gradual senescent decline in tibial growth rate, rate of chondrocyte proliferation, growth plate height, number of proliferative chondrocytes, number of hypertrophic chondrocytes, size of terminal hypertrophic chondrocytes, and column density. Estrogen treatment accelerated the senescent decline in all of these parameters. In senescent growth plates, epiphyseal fusion was observed to be an abrupt event in which all remaining chondrocytes were rapidly replaced by bone elements. Fusion occurred when the rate of chondrocyte proliferation approached zero. Estrogen caused this proliferative exhaustion and fusion to occur earlier. Our data suggest that (i) epiphyseal fusion is triggered when the proliferative potential of growth plate chondrocytes is exhausted; and (ii) estrogen does not induce growth plate ossification directly; instead, estrogen accelerates the programmed senescence of the growth plate, thus causing earlier proliferative exhaustion and consequently earlier fusion.